An Intriguing Case of Multisystem Inflammatory Syndrome in an Adult Patient with Remote Infection with COVID-19 and Acute Chlamydia - Madhuri Chandnani; William A. Charini; Anil Jha; Chetan Dodhia; Eduardo Haddad (Case Reports in Infectious Diseases)
Introduction. COVID-19 is associated with a broad range of immune inflammatory phenomena, with different manifestations in adults and children. We describe a case of COVID-19-related multisystem inflammatory syndrome in an adult (MIS-A), similar to that described in children (MIS-C), which may have been set off by an unrelated secondary infection. Case. A 27-year-old male patient presented with acute epididymitis secondary to acute Chlamydia infection that progressed to multisystem inflammatory failure with respiratory failure requiring endotracheal intubation and mechanical ventilation, cardiogenic shock with heart failure, and gastrointestinal and renal dysfunction. He tested negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by reverse transcriptase-polymerase chain reaction on a nasopharyngeal swab thrice within 4 days of presentation, but positive for SARS-CoV-2 immunoglobulin G antibody signifying remote infection. The patient was treated with tocilizumab and steroids, along with doxycycline for concurrent Chlamydia infection, resulting in dramatic improvement in all organ function. We suspect that C. trachomatis infection in this instance may have triggered an aberrant immune response that was shaped by prior exposure to SARS-CoV-2. Conclusion. We present a case of an adult patient with acute Chlamydia trachomatis infection occurring in the wake of asymptomatic (or at least unrecognized) COVID-19 resulting in MIS-A. Clinicians should be alert to the possibility of other such unusual reactions occurring in the aftermath of COVID-19. This case also highlights the importance for clinicians who care for adult patients of being familiar with the multisystem inflammatory syndrome of children, as an identical syndrome may occur in adult patients.